2016
DOI: 10.1007/s11250-016-1143-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic models for breed quality and navel development scores and its associations with growth traits in beef cattle

Abstract: Estimation and prediction ability of linear and threshold models for yearling breed quality score (BQ) and navel development score at weaning (WN) and yearling (YN), considering variances, heritabilities, and rank correlations based on the breeding values predicted for bulls, were compared. Furthermore, it was determined whether BQ, WN, and YN are genetically associated with growth traits (BWG: birth to weaning weight gain, WH: weaning height, WYG: weaning to yearling weight gain, YH: yearling height) to field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…For young Nelore bulls on pasture performance test stations, Lima et al (2013) found a slightly lower heritability for racial traits. Similarly, Boligon et al (2016) obtained a heritability of 0.15 for BQ score using part of the same population included in the present study. However, Faria et al (2009) and Reimann et al (2018) reported heritability of 0.21 and 0.32, respectively, for visual score of racial traits at yearling in Nelore and taurine breeds.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…For young Nelore bulls on pasture performance test stations, Lima et al (2013) found a slightly lower heritability for racial traits. Similarly, Boligon et al (2016) obtained a heritability of 0.15 for BQ score using part of the same population included in the present study. However, Faria et al (2009) and Reimann et al (2018) reported heritability of 0.21 and 0.32, respectively, for visual score of racial traits at yearling in Nelore and taurine breeds.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, Lima et al (2013) reported moderate genetic correlations between navel score and growth traits (0.28-0.44). Additionally, Boligon et al (2016) estimated genetic associations of 0.210 and À0.002 between navel score at yearling and weight gain from birth to weaning and from weaning to yearling, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pendulous navel increases risk of injuries and infection caused by friction against pasture [ 30 ]. During natural mating, bulls with long and pendulous navels are frequently exposed to injuries and trauma [ 31 ]. Expression of HMGA2 gene is also responsible for body size by regulating myoblast proliferation and myogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Navel length at yearling (NY) is an economically important trait in beef cattle raised in extensive production systems. A pendulous navel increases the risk of injuries caused by friction against the pasture, leading to infection, reproductive impairment and treatment expenses (Ashdown, 2006; Rabelo et al, 2008; Boligon et al, 2016). This trait is especially important to cattle raised in Brazil, the second largest beef exporter of the world, where Nellore ( Bos indicus ) animals compose the majority of the herds and approximately 88% of the females in reproductive age are subjected to natural mating (Asbia, 2016).…”
Section: Introductionmentioning
confidence: 99%